Exploring the determinants of crop-livestock diversification and its effect on farm income: Evidence from smallholder farmers in Homa Bay County, Kenya - Midamba, Dick Chune; Omondi, Samuel Onyango; Mose, Phoebe Bwari (International Journal of Sustainable Agricultural Research, 2025)
The integration of crops and livestock has been reported to have several benefits for farmers. It reduces farm risks, leading to increased output from crops and livestock. It also enhances household food production, resulting in improved household food security. Therefore, farmers are advised to incorporate as many crop types and livestock species as possible into their farms. However, the majority of farmers in Kenya tend to produce common crops such as maize and beans, alongside common livestock like cattle. This results in low crop-livestock diversification, which subjects many farmers to poor living standards. Consequently, it is imperative to assess the predictors and effects of crop-livestock diversification on farm income. This study evaluated the covariates influencing crop-livestock diversification and its effects on farm income in Homabay County, Kenya. Primary data were collected from 402 farmers using multistage sampling. The analysis employed propensity score matching and gross margin methods. The findings indicated that farm size, group membership, marital status, age, and gender significantly influence farmers’ crop-livestock diversification. The results also demonstrated that crop-livestock diversification increases farm income by KES 40,800 per acre (Nearest neighbor matching), KES 41,488 per acre (Kernel matching), and KES 36,132 per acre (Radius Matching). These findings underscore the importance of encouraging farmers to incorporate multiple crops and livestock into their farms through public sensitization. Extension agents should target young farmers and female-headed households when providing extension services. Finally, there is a need for public awareness campaigns among farmers regarding the benefits of crop-livestock diversification.